2019
DOI: 10.1071/py19021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding lived experiences of Aboriginal people with type 2 diabetes living in remote Kimberley communities: diabetes, it don't come and go, it stays!

Abstract: This study aimed to explore the lived experiences of Kimberley Aboriginal people with type 2 diabetes managed by remote Aboriginal Community Controlled Health Services using phenomenological analysis. Semi-structured interviews formulated by Aboriginal Health Workers, researchers and other clinicians were used to obtain qualitative data from 13 adult Aboriginal patients with type 2 diabetes managed in two remote communities in the Kimberley. Together with expert opinion from local Aboriginal Health Workers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This phenomenon is similar to that described, who mentioned that uninformed people can make inappropriate judgments toward healthcare behaviors ( 33 ). Consistent with the results of a study, we found that participants had limited access to health services which prevented them from being aware of their health status ( 34 ). However, such participants were living in a traditional way of life ( 9 , 33 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This phenomenon is similar to that described, who mentioned that uninformed people can make inappropriate judgments toward healthcare behaviors ( 33 ). Consistent with the results of a study, we found that participants had limited access to health services which prevented them from being aware of their health status ( 34 ). However, such participants were living in a traditional way of life ( 9 , 33 ).…”
Section: Discussionsupporting
confidence: 90%
“…We discovered that 51.5% of participants had a high level of HbA1c (>6.5). The effects of poor regulation of the HbA1c level on the body have been discussed extensively ( 23 , 33 , 34 ). Most participants in our study had a low educational level and insufficient income, which may have had a negative impact on their health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Routine activities for managing and controlling T2DM are required, and some participants reported that when they experienced high blood sugar levels, their children had to leave their jobs to take care of them and watch over them for complications at home or in hospital. As the literature shows, diabetes is a chronic disease, and patients may experience difficulty managing their disease as a lifelong journey and require long-term services appropriate for ethnic minority cultures and practices from healthcare providers [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that more than half of ethnic minority people obtained knowledge scores at low and moderate levels [7,31,32]. Some studies have shown that language differences are a major barrier to communication among patients and health personnel [33] and can result in miscommunication and misinformation during a health visit [34,35].…”
Section: Discussionmentioning
confidence: 99%